O sistema dinâmico de informações bibliográficas do Instituto de Pesquisas Rodoviárias do Departamento de Estradas de Rodagem: análise de desempenho - Barbosa, Ernani (1988)
The present work analyses the Instituo de Pesquisas Rodoviarias, computerized information system of the Departamento Nacional de Estradas de Rodagem. The Systemis strudied in a modular way; at first as it was designed, and subsequently analised in its present state. On the basis of this previous analysis, the performance of the system is analysed in the light of Information Science. Final conclusion are presented at the end of the work, accompanied by suggestions to improve the System.